The Effect of Cue Labeling in Multimedia Learning: Evidence From Eye Tracking - Hu, Jialu; Zhang, Jinkun (Frontiers in Psychology, 2021)
Cue labels are useful during multimedia learning. According to spatial contiguity principle, people learn more when related words and pictures are displayed spatially near one another. Well-arranged labels of multimedia material can greatly facilitate learning. This study used eye tracking to examine the joint influence of label size (large vs. small) and color (included vs. not) on multimedia learning. The results revealed that larger labels led to better retention test performance and a higher AOI glance count, but no cueing effect was found for color. Cues have a certain attention-leading function that promotes the learner remembering the content. These findings suggest that salient labels that provide explanatory information can guide learners' attention and facilitate learning, though a combination of label size and color salience did not demonstrate a superior cueing effect.